The Effect of an Anti-Bullying Intervention on Male Students' Bullying-victimization Behaviors and Social Competence: A Randomized Controlled Trial in Deprived Urban Areas - Salimi, Nooshin (J Res Health Sci, 2019)
Background: Violence among adolescents is a global public health concern. There is limited evidence on the effectiveness of anti-bullying interventions in Iran. Weaimed to examine the effectiveness of social cognitive theory (SCT)-based intervention on reducing bullying and victimization in elementary school students. Study design: A randomized controlled trial. Methods: Eight elementary schools (consisted of 280 students in 5(th) and 6(th) grade) from deprived and semi-deprived areas of Kermanshah (west of Iran) were randomly assigned to intervention and control group from 2018 to 2019. Anti-bullying training content appropriate for SCT and sociocultural characteristics were provided to the intervention group including students, parents, teachers and school staff. The measures included SCT constructs, bullying, victimization, and social competence of students. Results: At baseline participants of two groups were homogenous in terms of demographic factors except for the type of living with the parent (P=0.040) and outcome variables including SCT constructs and bullying behaviors. The interventions significantly improved SCT constructs, reduced bullying and victimization and increased social competence in the intervention group compared to the control group (P<0.001). The difference between outcome expectations in both groups was not significant (P=0.137). Conclusion: Interventions based on sociocultural characteristics and focuses on SCT theory reduce bullying and victimization behavior. Given the effectiveness and feasibility of these interventions, this theory can be effective to break the bullying cycle and improve social competence.